2009
DOI: 10.1007/s11661-009-0092-y
|View full text |Cite
|
Sign up to set email alerts
|

Slurry Erosion Characteristics and Erosive Wear Mechanisms of Co-Based and Ni-Based Coatings Formed by Laser Surface Alloying

Abstract: In the present work, an attempt has been made to study the slurry erosion properties and operating erosive wear mechanisms of Co-based Stellite 6 and Ni-based Colmonoy 88 coatings, and also to list the conditions at which maximum and minimum erosion rates occur. Laser surface alloying (LSA) has been done on 13Cr-4Ni steels with commercial Co-based Stellite 6 and Ni-based Colmonoy 88 powders. Slurry erosion tests have been conducted on LSAmodified steels for a constant slurry velocity of 12 m/s and for a fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Tested materials can be divided into following groups: ferrous [5,15], cobalt-based [4,16] nickel-based [2,7,11], titnium-based [4] materials and bulk metallic glasses (BMG) e.g. zirconium-based bulk metallic glass (Zr 44 Ti 11 Cu 10 Ni 10 Be 25 ) [2]. In case of ductile ferrerous materials, e.g.…”
Section: Slurry Erosion Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation
“…Tested materials can be divided into following groups: ferrous [5,15], cobalt-based [4,16] nickel-based [2,7,11], titnium-based [4] materials and bulk metallic glasses (BMG) e.g. zirconium-based bulk metallic glass (Zr 44 Ti 11 Cu 10 Ni 10 Be 25 ) [2]. In case of ductile ferrerous materials, e.g.…”
Section: Slurry Erosion Phenomenonmentioning
confidence: 99%
“…Among others jet type slurry device, this type of test rig is quite popular, it has been used by in Ref. [2,3,5,7,11,[40][41][42][43][44][45]. a) b) Fig.…”
Section: Jet Type Apparatusmentioning
confidence: 99%
“…Kesavan et al 18 observed various types of precipitates in Ni-base PTA deposits on 316L SS substrate which favored hardness and wear performance. Shivamurthy et al 3 examined the slurry erosion properties and erosive wear mechanisms of laser surface alloyed Colmonoy 88 and Stellite 6 powders deposited on 13Cr-4Ni steels and highlighted the role of angle of impingement and particle size on these properties. Similarly, Ramachandran et al 19 while investigating the role of different testing variables found that the slurry concentration had a greater influence on the wear rate of PTA deposits than the particle size, speed of rotation and slurry bath temperature.…”
Section: Introductionmentioning
confidence: 99%
“…It has been learnt from the literature that slurry erosion resistance of the target surface can be enhanced by improving the hardness of the target surface. Further, a thermal spray coating technique is one of the simple and economical methods for improving the hardness of the target surface [2][3][4][5][6][7][8]. Surface coatings with very good mechanical properties can be deposited by using High-Velocity Oxy-Fuel (HVOF) thermal spray process [9].…”
Section: Introductionmentioning
confidence: 99%